On phi-2-Absorbing phi‎-2-Absorbing Primary Hyperideals of A Multiplicative Hyperring - Mahdi Anbarloei (IndoMS, 2019)
‎Let R be a multiplicative hyperring‎. ‎In this paper‎, ‎we extend the concept of 2-absorbing hyperideals and 2-absorbing primary hyperideals to the context ‎‎φ‎‎-2-absorbing hyperideals and ‎‎φ‎‎-2-absorbing primary hyperideals. Let ‎‎E(R)‎‎ be the set of hyperideals of ‎‎R‎‎‎ and ‎φ : E(R) E(R) {φ}‎‎ be a function. A nonzero proper hyperideal ‎‎I‎‎ of ‎‎R‎‎ is called a ‎φ‎‎- 2-absorbing hyperideal if for all ‎x, y, z R, xoyoz I- φ(I)‎‎ implies‎xoy I‎‎ or ‎‎yoz I‎‎ or ‎‎xoz I‎‎. Also, a nonzero proper hyperideal ‎‎I‎‎ of ‎‎R‎‎ is called a ‎φ‎‎- 2-absorbing primary hyperideal if for all ‎x, y, z R, xoyoz I- φ(I)‎‎ implies‎xoy I‎‎ or ‎‎yoz r(I)‎‎ or ‎‎xoz r(I)‎‎. A number of results concerning them are given.